Ocular Hypertension The Knowns and Unknowns - Lanza, Michele (IntechOpen, 2021)
This book provides useful information to physicians for managing ocular hypertension, which is one of the more controversial ocular conditions. It examines the social aspects of the disease and the new technologies available for treating it. The information presented will help physicians better diagnose and manage this condition.